Personal Experience and Aesthetic Value of Artwork - Jackūnas, Žibartas (Pedagogika, 2014)
Traditional Western theoretic culture conceives the results of a manifestation of the world in a human experience as an outcome determined mainly by the apprehended phenomena themselves and their objective properties. Such one-sided approach to reality was properly subjected to criticism by phenomenology, philosophy of language, hermeneutics, and postmodern thought. The above-indicated currents of philosophical thought stress the interpretive nature of the world and its understanding as well as the role semantic experience of a person plays in a process of interpretation. The article has the purpose to show, how both a forenamed approaches to reality – traditional and interpretive – determine the conception of an artwork and its aesthetic value. Traditional mode of thought prompts the investigators to see an artwork as an objective thing or artifact. This approach naturalizes a work of art, neglects its semantic and communicative dimension, remains in the background the meaning of an artwork and its relation to experience of a person involved in the process of its interpretation. Interpretive or semantic approach opens the possibility to elaborate a conception of aesthetic value of artwork based on the following semantic tenets: 1) aesthetic value can be directly ascribed only to aesthetic experience which manifests itself in the process of interpretation of an artwork. The process is, in its nature, interpretive par excellence; 2) manifestation of meanings, which form a semantic content of aesthetic experience, presupposes an active participation of generalized experience of a person taking part in the process of interpretation of artwork; 3) substantial part of personal experience, involved in the process of manifestation of aesthetic values of an artwork, consists of meanings related to value-system of a person; 4) an axiological dimension of aesthetic value of an artwork is related to two conjoint factors: a) emotional response to the meaning, conceived in the process of aesthetic interpretation of artwork; b) the changes in semantic experience (generalized) of a person, especially in his value-experience. The article comprises a more detailed characterization of the principles lying at the ground of traditional and semantic approaches to the problem of aesthetic value of artwork.